How to get grant money in the humanities and social sciences - Folsom, Raphael Brewster (Yale University Press, 2019)
A valuable and engaging guide to applying for--and getting--grants in the humanities and social sciences Scholars in the humanities and social sciences need money to do research. This book shows them how to get it. In this accessible volume, Raphael Folsom shares proven strategies in a series of short, witty chapters. It features tips on how graduate students, postdocs, and young faculty members can present themselves and their work in the best possible light. The book covers the basics of the grant-writing process, including finding a mentor, organizing a writing workshop, conceptualizing the project on a larger scale, and tailoring an application for specific submissions. The book includes interviews with nine of the most respected scholars in the country, each of whom has evaluated thousands of grant applications. The first authoritative book on the subject, Folsom's indispensable work will become a must-have resource for years to come.